Hubungan Persepsi Dalam Pemakaian Media Elektronik Dengan Perilaku SeksualitasRemaja Pada Mahasiswa Semester VI Di Stikes Bina Sehat PPNI Mojokerto - Dwi Wahyuningsih, Binarti (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractPerception is intepretating process toward simulative by individual accept, while sexual behavior is all types of behavior which is caused by sexual desire. There are many factors which can influence perception and sexual behavior in teenagers, and one of them is electronic media. An interest in electronic media, the use of electronic media, and the intensity of using elektronic media can influence teenagers perception and sexual behavior. This study aims are to determine the correlation of perception using electronic media toward sexual behavior of teenagers six semester student in Stikes Rina Sehat PPNT Mojokerto. This study is a survey analytic study with Cross Sectional Study that conducted108 six semester student SI nursing education in Stikes Rina Sehat PPNT Mojokerto. The samples were selected by using purposive sampling technique. The variables measured in this study is perception using electronic media and sexual behavior. The result of Cross tabulation analyzed were there were 35 respondent (32,4%) have positive perception and sexual behavior, while there were 41 responden (37,9%) have negative perception and sexual behavior. The conclusion ofthese study is the electronic media are one of factors which have correlation toward teenagers positive or negative perception and sexual behavior. The teenagers are expected to be able to self control, use time with positive activities, wise to advantage electronic media, and there are policy from institution to give curfew restriction of activities student in campus.Keyword: Perception, Electronic Media, Teenagers, Sexual Behavior.